Análise microbiológica da cavidade interna de implantes dentais osseointegrados utilizando o checkerboard DNA-DNA hybridization - Lucena, George Alexandre de Barros (2014)
Introduction: Infiltration of organic fluids and microorganisms at the abutment/implant interface may result in bacterial infection of peri-implant tissues. Internal colonization of periodontal pathogens may be caused by bacteria trapped during installation or penetration of abutment/implant leakage. The aim of this study was to detect periodontal pathogens in the internal area of dental implants before loading. Materials and Methods: Seventy-eight implants in 32 partially edentulous subjects were selected for this evaluation. A bacterial biofilm sample of the internal surface of each implant was taken and analyzed for the presence of 40 microorganisms by checkerboard DNA-DNA hybridization, prior to installation of healing or any other prosthetic abutment. Discussion: Bacteria were detected in 20 patients (62.5%), distributed in 41 implants (52.6%). Forty-seven percent of implants showed no bacterial detection. Spontaneous early implant exposure to oral cavity during the healing period was not significant (P >0.05) to increase bacterial prevalence, but implants placed at mandible had higher bacterial prevalence than maxillary ones. Conclusion: The internal surface of dental implants can serve as a reservoir of periodontal pathogens for future implant/abutment interface.